How Do Traders in Padang City Allocate Their Assets? - Jayaputra Trihamadhi (CV. Vocezmi Learnov, 2025)
Monetary policy does not always operate smoothly or effectively, as it is influenced by societal patterns and behavior in asset allocation. The findings of this study, using a quota sampling approach, reveal that monetary assets—such as savings in formal financial institutions—are preferred by 74.80% of traders in Padang City, followed by savings in non-formal financial institutions and insurance products. The study further identifies that none of the traders allocate their assets in the form of bonds. In terms of physical assets, land becomes the primary option, preferred by approximately 30.08% of traders. Other forms of physical assets include buildings, gold, and livestock. Additionally, 86% of respondents reported having no awareness of monetary variables, such as interest rates and inflation. For traders in Padang City, interest rates do not serve as a consideration in their asset placement decisions. Consequently, monetary policy instruments relying on interest rate adjustments to regulate economic liquidity tend to be ineffective.